THE USE OF FACILITIES STRATEGY IN IMPROVING INDONESIAN STUDENTS’ LANGUAGE LEARNING OUTCOMES - Revi Mariska; Aswadi Jaya; Mega Prasrihamni (Esteem Journal of English Education Study Programme, 2024)
The purpose of this study is to ascertain whether class IV students at SDN 90 Palembang are able to improve their learning outcomes in Indonesian language proficiency through the usage of learning facilities. A pre-experimental approach using a one-group pretest-posttest design was employed in this study. The sample method used in this study was non-probability sampling combined with a saturated sampling methodology, and the population consisted of all 24 class IV students at SDN 90 Palembang. The paired sample t-test is the analysis method employed in the study. The questionnaire instrument's t test analysis findings show that there areWith a significance level of 0.05 and a significant value of 0.000 (two tailed), the result is rejected and accepted since the significant value is less than 0.05 and 1.713. Concurrently, the hypothesis positing that the test questions on learning outcomes were significant (two-tailed) was rejected and accepted at a significance level of 0.05, since the significant value was 0.000 < 0.05 and 1.713. Thus, it can be said that class IV students at SD Negeri 90 Palembang are learning more Indonesian as a result of their use of the learning facilities.30,310 > t_(hitung ) t_(hitung ) 9,737 > t_(tabel ) H_0 H_a t_(tabel) H_0 H_a.